The machine [videorecording (Blu-Ray)] - Biegel, Kevin; Landes, Scotty; Kreischer, Bert; Hamill, Mark; Tatro, Jimmy, 1992-; Babić, Iva; Maaser, Robert; Kurtzuba, Stephanie; Ford, Martyn, 1982-; Gabor, Jessica (Sony Pictures Home Entertainment, 2023)
Bert Kreischer rose to fame as a stand-up comedian known as The Machine, and in his signature set he recounts his true experience with Russian mobsters while on a booze-soaked college trip. Now, 23 years later, that trip has come back to haunt him as he and his estranged father are kidnapped back to Russia by the mob to atone for something they say he did. Together, Bert and his father must retrace the steps of his younger self amid a war within a sociopathic crime family, all while attempting to find common ground in their often fraught relationship.